Complexity Dynamic Analysis of Fractional-order Permanent Magnet Synchronous Motor in CNC Machine Tool. Issue 1 (March 2021) - Hai-yan, FU; Tengfei, Lei; Min, Su; Tingyang, Yan
Abstract: In this paper, permanent magnet synchronous motor system for fractional-order machine tools is studied. The nonlinear term of the system is decomposed by Adomian decomposition method, and the attractor and poincare cross-section of the system are drawn by Matalb. Meanwhile, the system is analyzed by numerical simulation including bifurcation diagram, SE complexity, C0 complexity and attractor phase diagram under parameter change, which further reveals the realizable dynamic characteristics of fractional-order chaotic system. The related research results lay a good foundation for the control of CNC ( Computer Numerical Control ) machine tools.